Potential Environmental Factors in Amyotrophic Lateral Sclerosis - Oskarsson, Björn (Neurol Clin, 2015)
The current state of research in environmental risk factors of ALS has provided many intriguing possible associations. Yet only one-smoking is at this time firmly established. The methodologic difficulties with studying a rare disease that occurs late in life, which could be related to exposures many decades ago, make relationships dauntingly difficult to prove. Despite continued improvement in methodology, significant challenges remain. The diagnostic criteria for ALS are complicated and there are continued efforts to improve them. As they are, the criteria do not yet capture all people with ALS, which further complicates epidemiologic studies. It is hoped that larger datasets with better characterization of different clinical features and laboratory markers will provide more robust estimates of risk factors in ALS in the years to come. A better understanding of environmental risk factors could help reduce exposures and it is hoped markedly reduce ALS incidence over time. Epidemiologic research is critical to advance this field, but the relative rarity of ALS and the current notion that exposures may affect the risk of ALS only decades later make such projects complex with many challenges. One US project of great potential is the National ALS Registry. It is a congressionally-mandated prospective population-based registry encompassing the entire US population. In addition to quantifying the incidence, prevalence, and demographics of ALS in the US, another main goal of the Registry is to examine the risk factors for the disease through online risk factor modules. There are currently 17 different risk factor modules that persons with ALS can complete including, but not limited to, cigarette smoking, alcohol consumption, military service history, occupational history, and a family history of ALS. Since the Registry's launch in October 2010, over 45,000 online risk factor modules have been completed. To our knowledge, this is the largest and most geographically diverse collection of risk factor data available about adults with ALS. Findings from these surveys may provide important insights into the pathology of ALS.